Sinergi KKN untuk Peningkatan Kesehatan dan Kesejahteraan di Dusun Pete - Fawwaz, Naufal; Yuniar, Zanuba; Adhi, Muhammad Abdillah Munadhil; Rahma, Amelia Dzakiyah; Kusumastuti, Amalia Hatmi; Nabilla, Nabilla; Maharani, Salsabiila Devita; Saputra, Daniel Ananta; Reyvanza, Muhamad Arya Hami; Putra, Raditya Bayu; Tinartayu, Seshy (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Synergy of KKN for Improving Health and Well-being in Dusun Pete aims to integrate academic knowledge with real-life conditions while fostering interprofessional collaboration in health solutions. Using a qualitative descriptive approach and community-based interventions, this program includes Family Care, counseling on Non-Communicable Diseases (NCDs) and Dengue Hemorrhagic Fever (DHF), as well as education on Clean and Healthy Living Behavior (PHBS) and dental health Through education and consistent treatment, the Family Care project helps patients with NCDs, especially those with hypertension, enhance their quality of life. Community understanding of risk factors, prevention, and disease management is increased by NCD and DHF counseling. Children's comprehension of oral health and personal hygiene is also improved by PHBS and dental health education in primary schools. According to the evaluation data, 26 of the 33 invited participants attended the NCD counseling session, resulting in a satisfactory attendance rate of 78%. A score of two for punctuality indicated minor scheduling delays. Given its relevance to the participants' needs, the delivered content received an excellent rating of 3. With a score of 3, participants showed a high level of enthusiasm and active participation in discussions and Q&A sessions. In the meantime, 55 of the 57 invited students showed up for the dental health and PHBS education session, yielding a 96% attendance rate—considered very good. The material's quality was assessed at 3, indicating excellent relevance and effectiveness, and punctuality was given a score of 3. However, participant excitement received a score of 2, indicating that additional participatory techniques are required to improve engagement. The cooperation of community service team, Posyandu cadres, and the neighborhood contributed to the program's success by guaranteeing sustained participation. All things considered, these initiatives have improved Dusun Pete's health and increased public knowledge of health issues, highlighting the need of a sustainable and cooperative strategy for wider community advantages.